2003
DOI: 10.1016/s0029-7844(02)02448-1
|View full text |Cite
|
Sign up to set email alerts
|

Is maternal obesity a predictor of shoulder dystocia?

Abstract: The strongest predictors of shoulder dystocia are related to fetal macrosomia. For obese nondiabetic women carrying fetuses whose weights are estimated to be within normal limits, there is no increased risk of shoulder dystocia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
2
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 18 publications
1
27
2
6
Order By: Relevance
“…In a study by Robinson et al, shoulder dystocia was found to be strongly related to foetal macrosomia; as in other studies, obesity was not an independent risk factor for shoulder dystocia [110,111]. It can be concluded that for obese women, the same predictors for shoulder dystocia apply as for nonobese women [111]. The risk of shoulder dystocia was 33% in vaginal deliveries of infants with birth weights >4,500 g and only 2% in infants with birth weights <4,500 g. These figures must be interpreted cautiously because they are based on a relatively small sample size [112].…”
Section: Labour and Deliverymentioning
confidence: 74%
See 1 more Smart Citation
“…In a study by Robinson et al, shoulder dystocia was found to be strongly related to foetal macrosomia; as in other studies, obesity was not an independent risk factor for shoulder dystocia [110,111]. It can be concluded that for obese women, the same predictors for shoulder dystocia apply as for nonobese women [111]. The risk of shoulder dystocia was 33% in vaginal deliveries of infants with birth weights >4,500 g and only 2% in infants with birth weights <4,500 g. These figures must be interpreted cautiously because they are based on a relatively small sample size [112].…”
Section: Labour and Deliverymentioning
confidence: 74%
“…The positive predictive value of obesity for predicting fatal shoulder dystocia is very low, 13/42,000 for BMI >35 kg/m 2 , and 4/10,000 for BMI >40 kg/m 2 [109]. In a study by Robinson et al, shoulder dystocia was found to be strongly related to foetal macrosomia; as in other studies, obesity was not an independent risk factor for shoulder dystocia [110,111]. It can be concluded that for obese women, the same predictors for shoulder dystocia apply as for nonobese women [111].…”
Section: Labour and Deliverymentioning
confidence: 87%
“…Adipöse Frauen gebären jedoch öfter makrosome Kinder oder leiden an Diabetes. Beides sind Risikofaktoren für die Schulterdystokie, bei deren Berücksichtigung keine unabhängige Assoziation zwischen Adipositas und erschwerter Entwicklung der Schulter festzustellen ist [22].…”
Section: Schulterdystokieunclassified
“…Others [62] found that 5% of extremely obese (over 250 pounds) women were found to have experienced shoulder dystocia. For obese non-diabetic women carrying fetuses whose weights were estimated to be within normal limits, there was no increased risk of shoulder dystocia [63]. The issue is further complicated by the decreased ability to accurately estimate fetal weight at the upper extremes of the growth curve, with errors exceeding 10% of the birth weight, in particular on the basis of suboptimal visualization [64,35].…”
Section: Labor and Deliverymentioning
confidence: 99%